Inter-population genetic diversity in Olea cuspidata subsp. cuspidata revealed by SSR and ISSR markers - Noormohammadi, Zahra (Acta Biologica Szegediensis, 2012)
The olive tree (O. europaea subsp. europaea var. europaea) is an ancient economic plant species with both cultivated and wild forms. In the present study, simple sequence repeat; SSR and inter simple sequence repeat; ISSR markers were used to study the genetic variation present in a few wild olive (O. europaea subsp. cuspidata) populations growing in the southern and western parts of Iran. Five SSR loci were analyzed which showed the presence of 12.6 alleles in average. The observed heterozygosity obtained for SSR markers ranged from 0.444 to 0.795 (mean value = 0.625), while Shannon index and polymorphic information content ranged from 1.46 (UDO99-043) to 2.47 (DCA3) and 0.620 (UDO99-43) to 0.871 (DCA3) respectively. Similarly ISSR analysis produced a total of 41 reproducible bands ranging from 240 bp (UBC-807) to 1750 bp (UBC823). The highest Nei’s genetic diversity as well as Shannon index was obtained for UBC823 locus (0.37 and 0.54 respectively). Kerman population had the highest mean number of alleles while Jareh population showed the lowest number of alleles. Analysis of molecular variation (AMOVA) showed significant difference (p < 0.05) both among and between olive populations for SSR supported by Fst pair-wise test. The highest value of within population ISSR genetic diversity occurred in Pahtak population, while Jareh population showed the highest value of among populations genetic diversity. UPGMA and NJ dendrograms obtained based on SSR and ISSR markers grouped the individuals of each population together in a distinct cluster, separated from the other populations due to their genetic distinctness.